Elite youth football goalkeepers outperform amateur adults in reactive agility task without a significant contribution of fatigue - Skala, F.; Kovác, K.; Zemková, E. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The performance of football goalkeepers (GKs) includes rapid changes in movement direction in response to visual stimuli. The available reactive agility tests, used to assess this ability, are sensitive enough to distinguish between field players of different performance levels [1,2]. However, there is a missing link in the reactive agility testing of football GKs. Furthermore, increasing repetitions of reactive tasks could produce fatigue, which is often neglected in the evaluation of reactive agility. Applying the novel "Football reactive agility for goalkeepers task" (FRAG), this study compares the reactive agility performance of elite youth and amateur adult GKs and analyses their changes in reaction speed with an increasing number of stimuli. METHODS: Eight elite youth (EY; 14.3±0.9 y) and eight amateur adult goalkeepers (AA; 21.6±1.3 y) underwent the reactive agility task, consisting of reaction to 8 light-based stimuli randomly displayed on 4 LED sensors (WittySEM, Microgate, Bolzano, Italy). These sensors were 2 m apart from the starting point and located at 30° and 60° angles. Participants ran and reacted to stimuli separated by 2 seconds with their hands. They performed 3 trials of the task with a 3-min rest interval. The best average reaction time of trials from the 2nd to the 7th stimulus was considered as a result of the FRAG task. Intraclass correlation (ICC) of the task with 95% CI was calculated. The Mann-Whitney U test with Cohen`s r effect size was used to compare the groups. These data are presented as median±SEM. The changes in reaction speed with an increasing number of stimuli were analysed using repeated measures ANOVA and Tukeys post hoc test. RESULTS: The ICC of the trials showed moderate to good reliability of the FRAG task (0.74-0.89). The average reaction time in the reactive agility task was shorter in the EY than in the AA group (*-0.04±0.014 s; -1.62%; p=.028; ES = .503, large effect). Repeated measures ANOVA showed non-significant differences between reaction times to consecutive stimuli in both the EY (F [7, 159] = 1.751, p = 0.10), and the AA group (F [7, 159] = 0.98, p = 0.45). CONCLUSION: The EY GKs outperformed the AA GKs in the FRAG task. Both groups were able to maintain their level of reaction speed when responding to an increasing number of stimuli. The influence of fatigue occurred as the "U-effect" with the lowest reaction times from the 2nd to the 5th response and further increases until the last 8th response. These changes were comparable in EY and AA groups. The FRAG task provides a potential evaluation method for the reactive agility assessment of football goalkeepers.